Evaluation of heavy metals in green algae Caulerpa lentillifera from Van Phong Bay and the bioaccumulation of copper in different concentrations in the laboratory - Nguyen, Thi Xuan Thuy; Nguyen, Nhat Nhu Thuy; Le, Trong Dung; Nguyen, Thi My Ngan; Le , Ho Khanh Hy; Dao, Viet Ha; Nguyen, Xuan Vy (Vietnam Journal of Marine Science and Technology, 2025)
In this study, morphological observation and genetic marker were applied to compare two clones, including natural Vietnamese and introduced clones. 11 elements of heavy metals in the algae collected from three different farms in Van Phong Bay were analyzed. In the laboratory, Caulerpa lentillifera was cultivated in different levels of Cu concentrations to evaluate the ability of Cu bioaccumulation and phytochelatin production of the algae. The results show that the morphological traits of erect frond and stalk between natural Vietnamese clones and introduced clones from Japan revealed significant differences but not ramuli diameter. Based on the tufA gene, there is no genetic differentiation between two clones, and Caulerpa lentillifera, C. germinata, C. cactoides, and C. bartoniae are sister species. The concentrations of Cd, Hg, and Pb from algae in Van Phong Bay were 0.10 (±0.017), 0.12 (±0.015), and 0.58 (±0.02) µg.g-1, repectively. In the seawater with 10 μM, algae showed the highest accumulation with 29.02 μg.g–1 in day 6, indicating the potential impact of the findings on understanding of heavy metal accumulation in marine algae.